2010
DOI: 10.1089/end.2009.0171
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Safety and Efficiency of Conventional Monopolar, Plasmakinetic, and Holmium Laser Transurethral Resection of Primary Non-muscle Invasive Bladder Cancer

Abstract: Both PK-TURBT and HoL-TURBT might prove to be preferable alternatives to CM-TURBT management of non-muscle invasive bladder cancer. PK-TURBT and HoL-TURBT, however, did not demonstrate an obvious advantage over CM-TURBT in tumor recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 18 publications
5
94
0
16
Order By: Relevance
“…The authors concluded that narrow band imaging with B-TURBT is an excellent alternative to traditional TURBT methods with the potential to improve current standards. Xishuang et al [11] compared M-TURBT, plasmakinetic, and holmium laser TURBT in 173 patients with primary NMIBC. Compared with the M-TURBT group, both plasmakinetic and holmium laser TURBT groups had less intraoperative and postoperative complications, including obturator jerk, bladder perforation, as well as bleeding and postoperative bladder irritation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that narrow band imaging with B-TURBT is an excellent alternative to traditional TURBT methods with the potential to improve current standards. Xishuang et al [11] compared M-TURBT, plasmakinetic, and holmium laser TURBT in 173 patients with primary NMIBC. Compared with the M-TURBT group, both plasmakinetic and holmium laser TURBT groups had less intraoperative and postoperative complications, including obturator jerk, bladder perforation, as well as bleeding and postoperative bladder irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Bolat et al [6] demonstrated that the use of bipolar diathermy had a significantly lower incidence of obturator jerk and bladder perforation. Xishuang et al [7] also showed a lower complication rate (including obturator jerk and bladder perforation) with the use of bipolar diathermy versus monopolar diathermy. In a large Japanese study carried out by Sugihara et al [8], bipolar resection was found to be associated with a significantly lower incidence of severe bladder injury when compared with monopolar resection.…”
Section: Preventing “Obturator Jerk”mentioning
confidence: 99%
“…Totally 173 patients were divided into 3 groups. Plasmakinetic group and holmium laser group were free from complications, while 4 perforations were seen in monopolar group (23). Intravesical approach technique which needle is inserted throughout cystoscopy has been used recently.…”
Section: Prevention Of Obturator Reflexesmentioning
confidence: 99%